Penerapan Metode MOOSRA dan ROC dalam Penentuan Guru Terbaik - Nazrul Azizi; Bella Putri Cahyani; Hetty Rohayani; Jasmir; Yuwan Jumaryadi; Jeperson Hutahaean (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The best teacher is a teacher who is given appreciation because he has a high achievement value. There are several specific criteria in selecting the best teacher, namely in terms of achievement, skills possessed, morals/manners, and discipline. To improve quality in the world of education, of course, a teacher is needed who will interact directly with students in the learning process which can indirectly improve the quality of education. With the interaction in the learning process, it is hoped that it will become a resource in improving the quality of education. There is also something the government is doing that is in a way to advance education, namely by empowering teachers and giving an award, especially for those who are entitled to get the title of the best teacher with achievements. Based on the results of interviews and research related to SMK Negeri 2 Medan, in determining the best teacher the assessment is still in a subjective way. This is based only on the opinion of each teacher and does not start with certain criteria, this will affect social events because the method used is not in an objective way and ends in an unfair feeling caused by subjective methods among fellow teachers who teach at the school. Therefore, it is recommended that schools must determine and agree on certain criteria in determining outstanding teachers, even though the assessment in the final process is still carried out by voting from those who have voting rights in determining the outstanding/best teachers, which of course is also carried out by teachers. The system for determining the best teacher is always a problem every year because it can create injustice among fellow teachers. Therefore, to facilitate and eliminate this unfair attitude, a decision support system (SPK) is needed which can facilitate the determination of the best teacher at SMK Negeri 2 Medan. A decision support system is an interactive computer system that can assist decision making by utilizing existing data to solve unstructured and semi-structured problems. In this SPK there are several methods, one of which is the Moosra Method (Multiobjective Optimization on the Basis of Simple Ratio Analysis) and the ROC (Rank Order Centroid) Method. The result of ROC and MOOSRA method calculation showed that Halimah (A10) obtained the highest final preference value of 14.599, making her selected as the best teacher.